The Risk of Nanotechnology: A Challenge to the Insurance Industry - Sliwinski, Adam; Lomott, Marietta Janowicz- (Journal of Reviews on Global Economics, 2020)
Nanotechnology poses a challenge for the modern man. Aside from the many benefits that nanotechnological growth may bring, it exposes our civilization to an increasing number of new risks, creating hazards that are currently difficult to foresee. Nanotechnological developments may have a negative impact on the natural environment; some researchers claim that they may even jeopardize the very existence of humankind. Existence of defined threats opens up space for the functioning of insurance. Answering the need for nanotechnological risk management, the insurance sector should develop a strategy that would offer a reduction of risk aversion (especially among producers) and augment further development of nanotechnology-based production methods. However, this leads to questions whether nanotechnology-related risk is an insurable risk and whether it is technically feasible at this time to draft such an insurance offer. The present publication attempts to answer these questions.